Health Risk Assessment of Heavy Metals in Selected Root Vegetables - Cezara Voica; Carmen Roba; Andreea Maria Iordache (Innovations in Biological Science Vol. 3, 2024)
Food safety is an increasing concern, and the rising demands for this have drawn the attention of researchers to the risks associated with consuming contaminated vegetables. Health risk assessment is beneficial in providing information about any threat regarding heavy metal contamination in vegetables. The concentrations of heavy metals were analysed in over 100 root vegetables collected from the Romanian area. The inductively coupled plasma mass spectrometry technique (ICP-MS) was used for the determinations. The risk associated with the consumption of vegetables was assessed by calculating the hazard quotient. With only a few exceptions, the estimated daily intake of heavy metals associated with the radishes, carrots, and potatoes ingestion was within the provisional tolerable daily intake, indicating that the concentration of heavy metals received by the body cannot negatively impact consumers’ health.